Development of Power Point-Based Learning Media Using Google Slides on Tharah Material for Class VII Students at MTs DDI Takkalasi - Khaerun Nisa; Muh. Dahlan Thalib; Buhaerah; Muhammad Saleh; Usman (Universitas Muhammadiyah Palu, 2024)
This research was conducted with the aim of developing power point-based learning media using Google Slides on thaharah material. The learning media developed is used to make it easier for educators to deliver learning material in a more interesting way. This research was conducted by adopting the ADDIE development model which includes stages (Analyze, Design, Development, Implementation, Evaluation) including: (1) analysis, (2) product design, (3) development, (4) product implementation, (5) evaluation . Learning media was developed based on Power Point using Google Slides. The media that had been developed and passed expert and material validation tests were then tested on a limited basis with 5 people and on a large scale with 28 randomly selected class VII students at MTs DDI Takkalasi. The results of this research are in the form of power point-based learning media using Google Slides on thaharah material. The validity test was carried out twice, namely the media validity test with the results obtained an average of 3.2 which was categorized as very feasible in the appearance aspect and in the usage aspect, so an average of 2.6 was obtained which was categorized as feasible. At the material validation test stage, an average score of 3.33 was obtained, which was categorized as very feasible. Meanwhile, in the